Effect of rotating and oscillating blade on the heat transfer enhancement of non-Newtonian fluid flow in a channel. (25th February 2017) - Izadpanah, Ehsan; Babaie Rabiee, Marzie; Sadeghi, Hosein; Talebi, Shahram
Highlights: The effect of oscillating and rotating blade on the heat transfer enhancement was investigated. The heat transfer has increased in the presence of the blade. For power law index larger than 0.8 the highest rate of heat transfer is related to oscillating blade. For power law index smaller than 0.6 the highest rate of heat transfer is related to stationary blade. In all the cases, the highest pressure drop was related to the stationary blade. Abstract: In the present work, the effect of rotating and oscillating blade on heat transfer enhancement of Newtonian and non-Newtonian fluid flow in a channel is investigated numerically. The non-Newtonian fluid with shear thinning and shear thickening behavior is modeled by the power-law relationship. The results are presented for local and average Nusselt number, pressure drop and temperature and vorticity contours for various power law indexes. Depending on the power law index, the rotating or stationary blade can have more effects on heat transfer. Also, it is observed that by increasing power law index the value of heat transfer decreases. Comparing the results of channel with and without the blade, it can be found that the presence of the blade for all power law indexes has a positive effect on the heat transfer enhancement. The maximum heat transfer enhancement to straight channel is 58.7% for a stationary blade with n = 0.4.